Social change among the pioneers of sociology - boussakra, omer (Journal of Social Sciences and Humanities, 2020)
A study in sociology is not free to address the subject of social change; either as an input to the analysis through the use of theories of change, or to reach at the end of these studies that social change is the first and last reason for the emergence of some social phenomena or problems. The concept of social change is one of the traits that have afflicted mankind to the present time. Change refers to the changes and changes that take place in the construction of any society in the presence of driving forces that contribute in one way or another to the change during a certain period of time. Therefore, in order to use these theories or to facilitate conclusions, we must identify the roots of this issue, which has become the basis for the emergence of different schools and theories of social change that try to provide an explanation for social change, by changing its causes, based on a set of philosophical hypotheses and perceptions. This explains the phenomenon of social change.It is not based on scientific and empirical research, but looks at social change in general and one in societies as a whole, and does not give importance to the difference of space or time, and provide general and comprehensive provisions, that is, it speaks of humanity and change itas a whole. This paper dealt with the most important ideas and perceptions of sociologists as attempts to understand the subject of social change, which was occupied by many scientists, thinkers, philosophers, historians and anthropologists, these ideas which were the first roots of social theories in force to this day; Circular theories, diffuse theories ...